HS-5 and HS-27A Stromal Cell Lines to Study Bone Marrow Mesenchymal Stromal Cell-Mediated Support to Cancer Development - Adamo, Annalisa; Delfino, Pietro; Gatti, Alessandro; Bonato, Alice; Takam Kamga, Paul; Bazzoni, Riccardo; Ugel, Stefano; Mercuri, Angela; Caligola, Simone; Krampera, Mauro (Frontiers in Cell and Developmental Biology, 2020)
In this study, we compared the overall gene and pathway expression profiles of HS-5 and HS-27A stromal cell lines with those of primary bone marrow MSCs to verify if they can be considered a reliable alternative tool for evaluating the contribution of MSCs in tumour development and immunomodulation. Indeed, due to their easier manipulation in vitro as compared to primary MSC cultures, several published studies took advantage of stromal cell lines to assess the biological mechanisms mediated by stromal cells in influencing tumour biology and immune responses. However, the process carried out to obtain immortalised cell lines could profoundly alter gene expression profile, and consequently their biological characteristics, leading to debatable results. Here, we evaluated the still undisclosed similarities and differences between HS-5, HS-27A cell lines and primary bone marrow MSCs in the context of tumour development and immunomodulation. Furthermore, we assessed by standardised immunological assays the capability of the cell lines to reproduce the general mechanisms of MSC immunoregulation. We found that only HS-5 cell line could be suitable to reproduce not only the MSC capacity to influence tumour biology, but also to evaluate the molecular mechanisms underlying tumour immune escape mediated by stroma cells. However, HS-5 pre-treatment with inflammatory cytokines, that normally enhances the immunosuppressive activity of primary MSCs, did not reproduce the same MSCs behaviour, highlighting the necessity to accurately set up in vitro assays when HS-5 cell line is used instead of its primary counterpart.